TCM Therapeutic Approaches for Lung Cancer Inspired by the Huangdi Neijing - Zhao, Yaxuan; Zhao, Yanli; Liu, Lu (Journal of Contemporary Medical Practice, 2026)
This review systematically explores traditional Chinese medicine (TCM) therapeutic modalities for lung cancer from the theoretical perspective of the Huangdi Neijing (Yellow Emperor’s Internal Classic). By dissecting the etiopathogenesis, therapeutic principles and relevant treatment methods recorded in this canonical text, combined with modern clinical characteristics of lung malignant tumors, this paper elaborates on the clinical application of vital qi-supporting and pathogen-eliminating therapy, treatment conforming to pathogen tendency, emotional regulation, dietary conditioning and physical rehabilitation for lung cancer management. It aims to provide theoretical basis and practical guidance for clinical TCM practice, elevate the therapeutic efficacy of TCM interventions for lung cancer, and improve patients’ overall quality of life.